The Effect Cytotoxic and Apoptotic Propagation Chloroform Fraction of Ocimum sanctum L. Towards Hela Cells Line Culture - Ghani Nurfiana Fadma Sari; Sri Rejeki Handayani (Biomedika, 2020)
Materials used in the research are Ocimum sanctum L, a herbaceous shrub used in traditional medicine displaying as immunomodulator, anti-stress, hepatoprotective, kemopreventif, and anti-inflammatory. A research to identify its ethanol extract of Ocimum sanctum has been conducted, showing that it possesses cytotoxic activities to HeLa cells with IC50 value of 209µg/ml. The aim of this research is to find out activities cytotoxic and apoptotic propagation chloroform fraction of Ocimum sanctum towards HeLa cells line. The extraction was done using maceration using ethanol 96% solvent and fractionation was done using chloroform. Effects of chloroform fraction on HeLa cells were tested using MTT at various dosages (500, 250, 125, 62.5, and 31.25) µg/ml. Cisplatin (Kalbe) was applied as positive control. The effect apoptotic propagation chloroform fraction of Ocimum sanctum on HeLa cells was observed by DNA painting method using orange ethridium bromide-acridine. The test results showed that the chloroform fraction of Ocimum sanctum extract on HeLa cells had an IC50 value of 155.67 µg / ml ± 46.99 and Cisplatin had an IC50 value of 16.81 µg / ml ± 20.37. Double staining test shows the existence of cells undergoing apoptosis. Based on these results, the chloroform fraction Ocimum sanctum has been shown to be cytotoxic and has the possibility of stimulating apoptosis of cervical cancer cells (HeLa). This can be used as a basis for the development of these plants as anticancer agents with specific action targets.